Diagnóstico social dos catadores de resíduos vinculados às Associações de Catadores de Material Reciclável do Município de Vitória-ES - Micaela, Jádia Petri Penholato (2013)
The challenge of municipal administrations is to find viable solutions to waste management, including participation of waste pickers, as proposed in the National Policy on Solid Waste. The city of Vitória - ES hosts two associations of waste pickers named Amariv and Ascamare, wich have 45 pickers, who are responsible for segregate monthly 110 tons of recyclable solid waste. This research tender a diagnosis of waste pickers that work at associations and suggest actions that enable to increase both production and quality of life at work of these professionals. The results are obtained from a literature search combined with meetings that involve interview and a questionnaire to the Vitoria City Hall (PMV) employees and the Amariv and Ascamare associated. The results show that the social characteristics of the associated Amariv and Ascamare are similar. Most respondents are in the age group 37-56 years and have low education level. Few of them are still studying. Women are the majority in the group. The majority of respondents have less than ten years of experience with waste picking and a small part of them has worked as a standalone picker, but 75% of them claims to suffer prejudice due the occupation. Most respondents live in Vitoria and they seek medical and dental health services regularly. The investigation of respondents’ perception about working conditions, it was compared with the perception of PMV as an external view. It is observed that, in some aspects, such as the structure of the workplace and the conditions of the machinery, PMV is less critical than the associations. In other aspects, such as bulk of waste, work safety, cleaning and nutrition, PMV is more critical than the associations. In actions that directly involve PMV, such as the support provided by her and the communication between her and associations, PMV’s opinion support the associations’ opinion. Generally, the investigation of respondents’ perception demonstrates the precariousness of the structure of associations and working conditions of waste pickers who work at Amariv and Ascamare, concluding that they need improvements, which are proposed at the end of the research